A Chart Review Study of Sexually Transmitted Infections Among Persons Living with HIV Attending an STI Clinic in Trinidad. (13th November 2019) - Edwards, Jeffrey; Hinds, Avery; Lyons, Nyla; Edwards, Jonathan; Quammie, Shauntelle; Figueroa, John Peter
A chart review study of the sexually transmitted infection (STI) prevalence among persons living with HIV (PLHIV) was conducted among STI clinic attendees in Trinidad between January 2012 and December 2012. Data were abstracted from client records to obtain the clinical and the laboratory diagnoses of STIs. Descriptive and bivariate analyses were conducted, and factors significantly associated with the presence of a STI were assessed using multiple logistic regression. During this period, 385 PLHIV were seen; 104 (27.0%) were newly HIV diagnosed and 281 (73.0%) had a known history of HIV infection; 135 (35.1%) were diagnosed with a STI. Patients with known HIV infection were more likely to be diagnosed with a STI than those who were newly diagnosed (odds ratios: 6.99; 95% confidence interval: 3.79-12.89). The STI prevalence was high among PLHIV in Trinidad, identifying them as a critical target group for public health interventions to prevent the spread of HIV and STIs.